Indicadores de gestión de la Dirección Administrativa de la Empresa CNEL del cantón Babahoyo - Peña Mendoza, Yolanda del Pilar (2020)
The research study is carried out with the objective of analyzing the management indicators in the Administration Directorate of the public company CENEL (National Electricity Center), an institution that is responsible for the administration and supply of the electric service to the citizens of the canton, where administrative weaknesses were detected in terms of resource management, constant turnover of staff, lack of addressing and training of servers working in the institution, responsibilities that fall under the Administration Directorate, which, if not fulfilled, directly affect the scope of organizational objectives and efficient delivery of electricity service to citizens. The findings detected were obtained through the implementation of the type of field research, together with the inductive method and the survey as a technique, data that allow us to conclude that the management indicators established by CNEL EP as part of its organizational development are not they execute fully, which causes a general malaise of the population, a situation that impacts their institutional image.